Preparation and characterization of polylactic acid based polyurethane for environmental friendly packaging materials - Ismail, Muhamad Norshafiq; Rafidi, Najihah; Awale, Raina Jama; Ali, Fathilah (Penerbit Akademia Baru, 2017)
Conventional packaging materials are mostly produced using petroleum-based substances and its’ non-biodegradability are causing landfill problems. Therefore, researches have been done to replace the non-degradable polymer substances to degradable polymers. Polylactic acid (PLA) is a type of biodegradable polymer which is brittle but has good mechanical strength, which makes it a suitable polymer to be used as packaging materials. To improve the flexibility of PLA, PLA based polyurethanes (PUs) are produced by using PLA-diol with vegetable oil polyol as the chain extender. Palm oil polyol (PO) is a type of vegetable oil polyol which are used in various productions of PUs. In this study, PO polyol is used as soft segment to improve the flexibility of PLA whereas hexamethylene diisocyanate (HDI) and toluene diisocyanate (TDI) are used as a source of isocyanate. PLA/Palm oil polyol based polyurethanes (PLAPOPUs) are synthesized using one-shot and two steps polymerization method. Fourier Transform Infra-Red (FT-IR) spectra confirmed on the formation of urethane bond and glass transition temperature was analyzed using Differential Scanning Calorimetry (DSC). The PLAPOPU prepared using HDI through one-step method has high potential to be used in environmental friendly packaging industries.